2021
DOI: 10.3389/fpubh.2021.798746
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Hospital Admission for Asthma in Children From Short-Term Exposure to Air Pollution: Case-Crossover Evidence From Northern China

Abstract: Background: Previous studies suggested that exposure to air pollution could increase risk of asthma attacks in children. The aim of this study is to investigate the short-term effects of exposure to ambient air pollution on asthma hospital admissions in children in Beijing, a city with serious air pollution and high-quality medical care at the same time.Methods: We collected hospital admission data of asthma patients aged ≤ 18 years old from 56 hospitals from 2013 to 2016 in Beijing, China. Time-stratified cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Our study was not without some seasonal heterogeneity. Generally, the adverse effects of PM 2.5 , PM 10 , and NO 2 were noted to be slightly higher in warmer as compared to colder months, consistent with findings reported by previous studies performed in Beijing ( 79 ), Fuzhou ( 80 ), Taiwan ( 81 ), and Hong Kong ( 82 ). The reasons why air pollutants are more harmful in a warmer season can be explained by high temperature itself being associated with increased risk of pneumonia ( 83 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our study was not without some seasonal heterogeneity. Generally, the adverse effects of PM 2.5 , PM 10 , and NO 2 were noted to be slightly higher in warmer as compared to colder months, consistent with findings reported by previous studies performed in Beijing ( 79 ), Fuzhou ( 80 ), Taiwan ( 81 ), and Hong Kong ( 82 ). The reasons why air pollutants are more harmful in a warmer season can be explained by high temperature itself being associated with increased risk of pneumonia ( 83 ).…”
Section: Discussionsupporting
confidence: 91%
“…The main culprit in that study was the gaseous air pollutant, sulfur dioxide (SO 2 ), particularly in the younger age group [31]. Zhao et al [33] demonstrated an increased risk for pediatric asthma hospitalization with higher levels of short-term exposure to PM 2.5 , SO 2 and NO 2 [32]. The impact of smaller particles size was demonstrated by a recent study conducted in China, where the smaller the particle size the stronger the observed effect estimates associated with increased outpatient department visits due to asthma.…”
Section: Pollutant Exposures and Asthma Morbiditymentioning
confidence: 99%
“…Influenza was independently linked to a higher risk of AMI according to prior research [21], and meteorological factors had an adverse effect on cardiovascular diseases [21][22][23][24], so the influenza endemic, daily mean temperature, and relative humidity were regarded as the confounding factors and were adjusted in our statistical model. When the positive rate of influenza virus isolation in any given week exceeded 20% of the highest weekly positive rate in the observation season in the north of China, it was defined as the influenza endemic (IF) [25,26], based on the data provided by the Chinese National Influenza Center [27]. The China Meteorological Administration provided the daily mean temperature and relative humidity.…”
Section: Data Gatheringmentioning
confidence: 99%